2020
DOI: 10.1080/13625187.2019.1709963
|View full text |Cite
|
Sign up to set email alerts
|

Depo-medroxyprogesterone acetate, weight gain and amenorrhea among obese adolescent and adult women

Abstract: Purpose:The objective of the current study was to evaluate the correlation between obesity and the use of depo-medroxyprogesterone (DMPA) in regards to weight gain and changes in bleeding patterns. Materials and Methods:A retrospective chart review of women receiving 150mg DMPA via intramuscular injection at inpatient and outpatient clinics at the University of Mississippi Medical Center (UMMC) between June 1, 2012 to December 31, 2016 was conducted. Body mass indices (BMI) were assessed at baseline and at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…The results showed that the use of DMPA for more than 3 years has a greater risk of developing obesity. Previous research also showed the same results, where the use of DMPA led to obesity [6], [10], [15], [22].…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…The results showed that the use of DMPA for more than 3 years has a greater risk of developing obesity. Previous research also showed the same results, where the use of DMPA led to obesity [6], [10], [15], [22].…”
Section: Methodssupporting
confidence: 69%
“…Contraceptive methods related to weight gain in several studies, namely Depo Medroxy Progesterone Acetate (DMPA) contraception [6], [25]- [27]. In line with this study, the use of DMPA hormonal contraception increases the incidence of obesity which is triggered by excessive weight gain.…”
Section: Methodsmentioning
confidence: 60%
“…Depot medroxyprogesterone has the largest effect on increased weight, while other oral contraceptives have either neutral or only slight increase. 18,28 In a primarily African American sample (87.7%), adolescents had increased weight gain compared to adult women, with mean increases of 5.35 ± 1.4 kg vs 1.75 ± 0.56 kg, respectively (P = 0.01). 28 If long-acting contraception is a goal, the most weight neutral and effective are the progesterone-containing intrauterine devices.…”
Section: Contraceptionmentioning
confidence: 98%
“…18,28 In a primarily African American sample (87.7%), adolescents had increased weight gain compared to adult women, with mean increases of 5.35 ± 1.4 kg vs 1.75 ± 0.56 kg, respectively (P = 0.01). 28 If long-acting contraception is a goal, the most weight neutral and effective are the progesterone-containing intrauterine devices. 29 Further, combined oestrogen-progestin contraceptives carry some increased risk of venous thrombosis, 30 as well as impact on bone accrual, 31 making progestin-only a preferred means of birth control.…”
Section: Contraceptionmentioning
confidence: 98%
“…According to a systematic review and meta-analysis, progesterone-only pill and DMPA users had no change in BP, myocardial infarction, or stroke compared to nonusers [26]. One concern with DMPA, an injectable progesterone, is the potential increased risk in venous thromboembolism and weight gain, though studies reporting these associations have been mixed and observational only [26][27][28][29]. Progesterone-only pills and DMPA may be preferred for women with HTN who want to avoid an implantation procedure inevitable with long-acting reversible contraceptives.…”
Section: Temporal Trends In Contraception Usementioning
confidence: 99%